2022
DOI: 10.1126/sciadv.abo1190
|View full text |Cite
|
Sign up to set email alerts
|

Differences in ion-RNA binding modes due to charge density variations explain the stability of RNA in monovalent salts

Abstract: The stability of RNA increases as the charge density of the alkali metal cations increases. The molecular mechanism for this phenomenon remains elusive. To fill this gap, we performed all-atom molecular dynamics pulling simulations of HIV-1 trans-activation response RNA. We first established that the free energy landscape obtained in the simulations is in excellent agreement with the single-molecule optical tweezer experiments. The origin of the stronger stability in sodium compared to potassium is found to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The Li + ion has the highest charge density of the ions studied here. Some studies postulate that increased charge density of ions leads to increased stability of dsRNA . The Li + ion has also been shown to increase the stability of a glycine residue in silico due to an increase in water density around the carboxylate group of the residue and the presence of the first hydration shell of the Li + ion, a feature unique to this ion compared to other alkali metal ions .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The Li + ion has the highest charge density of the ions studied here. Some studies postulate that increased charge density of ions leads to increased stability of dsRNA . The Li + ion has also been shown to increase the stability of a glycine residue in silico due to an increase in water density around the carboxylate group of the residue and the presence of the first hydration shell of the Li + ion, a feature unique to this ion compared to other alkali metal ions .…”
Section: Discussionmentioning
confidence: 57%
“…These findings were surprising considering Li + has been shown to have a higher affinity for the ion atmosphere compared to Na + . , Both K + and Na + were shown to have relatively the same affinity for the ion atmosphere. These findings were contradictory to recent studies that suggested K + aggregates around the phosphate backbone more so than Na + . One may assume that increased aggregation would lead to increased stability; however, that association may not be the case here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Mg 2+ , the Na + ions have a weaker solvation shell, leading to frequent dehydration events and almost equal Coulombic forces between hexahydrated divalent magnesium cations and dehydrated monovalent sodium cations. The larger size of K + ions leads to a weaker hydration shell compared to Na + . , This property also facilitates the direct binding of K + ions to the DNA surface, causing them to compete with Mg 2+ ions for DNA binding (see Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…[30] Regarding the interaction to RNA, several studies reported that Na + condenses more onto the RNA than K + and that this effect induces larger stability of RNA by Na + compared to K + . [7,31,32] Further studies are needed to understand the extent to which monovalent cations affect actual biological processes in living cellular environment.…”
Section: Introductionmentioning
confidence: 99%